The Application of Final and Binding Principles in Sharia Economics Dispute Resolution Through Basyarnas - Dewi Nurul Musjtari; Riki Ali Nurdin (Kanun Jurnal Ilmu Hukum, 2021)
This study aims to determine the application of the final and binding principles in sharia economic dispute resolution through Basyarnas. This research method used empirical research with secondary and primary data. Secondary data was complemented by primary and secondary legal materials, while primary data was obtained through interviews. The data analysis was carried out in a descriptive qualitative manner. The results indicated that the final principle is applied to the settlement of sharia economic disputes through Basyarnas when the parties have received the sharia arbitration decision and do not object to the decision issued by Basyarnas, or when one of the parties submits an objection to the sharia arbitration decision, and the arbitrator re-signed the revised decision in accordance with Article 58 of Law Number 30 of 1999 and Article 20 of the 2017 Basyarnas Rules of Procedure. The final sharia arbitration decision will have binding power for the parties (binding) after the decision is registered with the Religious Court in accordance with the respondent’s regional laws.